Evaluation of an immunochromatographic test for feline AB system blood typing. (11th August 2015) - Spada, Eva; Proverbio, Daniela; Baggiani, Luciana; Bagnagatti De Giorgi, Giada; Perego, Roberta; Ferro, Elisabetta
Abstract: Objective: To determine the accuracy of an immunochromatographic cartridge (IC) test for blood typing feline type A, B, and AB blood samples. Design: Prospective observational study. Setting: University teaching hospital. Samples: Fifty‐one nonanemic and 19 anemic feline blood samples. Interventions: Samples were blood typed by both card agglutination (CA) and IC techniques. Discordant results were analyzed using a back‐typing technique for the presence of alloantibodies. Repeatability and reproducibility of the IC method were evaluated. Accuracy of the IC method was determined for feline whole blood anticoagulated with EDTA and citrate phosphate dextrose adenine (CPDA1), for feline‐packed RBCs with CPDA1 and saline adenine glucose‐mannitol, and for autoagglutinated and hemolytic samples. Accuracy of IC testing was determined for feline blood after room temperature, 4 ± 2, −20, and −80°C storage following 24, 48, 72, and 96 hours, and after 1, 2, 3, and 4 weeks of storage. Measurements and Main Results: In anemic and nonanemic samples the IC technique had a specificity, sensitivity, positive predictive value, and negative predictive value of 100% in detecting feline blood types A, B, and AB, outperforming a CA test. Results were repeatable and reproducible. Using IC it was possible to blood type samples anticoagulated with EDTA and CPDA1, packed RBC samples with CPDA1 and saline adenine glucose‐mannitol, autoagglutinated and hemolytic samples, and samples stored at 4 ± 2°C and at room temperature for up to 1 month. Conclusions: The IC technique is an accurate assay for the identification of A, B, and AB blood types in anemic and nonanemic feline blood. It has a higher sensitivity and specificity than the CA test, and can be used in samples stored with common anticoagulants or preservative solutions used in feline transfusion medicine.